2018
DOI: 10.1007/s00227-018-3426-8
|View full text |Cite
|
Sign up to set email alerts
|

Habitat with small inter-structural spaces promotes mussel survival and reef generation

Abstract: Spatially complex habitats provide refuge for prey and mediate many predator–prey interactions. Increasing anthropogenic pressures are eroding such habitats, reducing their complexity and potentially altering ecosystem stability on a global scale. Yet, we have only a rudimentary understanding of how structurally complex habitats create ecological refuges for most ecosystems. Better informed management decisions require an understanding of the mechanisms underpinning the provision of physical refuge and this ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…The mortality risk due to predation was reduced in reefs with small interstructural spaces (Bertolini et al, 2018). One study showed that the presence of the Pacific oyster ( Crassostrea gigas ) deterred predator attacks from mussels and reduced their mortality risk (Waser et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality risk due to predation was reduced in reefs with small interstructural spaces (Bertolini et al, 2018). One study showed that the presence of the Pacific oyster ( Crassostrea gigas ) deterred predator attacks from mussels and reduced their mortality risk (Waser et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In the context of the understanding of the success of M. galloprovincialis as an invasive species in South Africa, interactions were reported between the location, site or zone on the mussel mortality risk (Bownes & McQuaid, 2010; Marquet et al, 2013). In M. edulis , three studies explored solutions to limit the impact of predation on mussel production or populations and found statistically significant interactions between mussel size and either farming material by showing that protective socking material was more efficient in large mussels against diving ducks (Dionne et al, 2006), characteristics of the site by reporting that clumped habitats were more protective for small mussels against crab or starfish (Bertolini et al, 2018), or the presence of oysters Crassostrea gigas by showing that this presence significantly reduced the mortality of small‐sized mussels, but the effect varied according to crab size (Waser et al, 2015). Another study reported the effect of hypoxia‐induced stress on mussel mortality to be size‐specific, with larger mussels having an increased mortality risk under hypoxia conditions than smaller ones (Altieri & Witman, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…We also suggest this trade-off avoidance may be attained by encouraging methods that will avoid burial from the biodeposition activity of other mussels. Previous studies have found the addition of a shell substratum to be useful in avoiding competition and ensuring some protection from other stressors (Bertolini et al 2018(Bertolini et al , 2017Capelle et al 2019). In conclusion, we suggest that the three dimensional aspects of patterns should be studied in more detail, and that in order to optimise culturing, trade-offs between competition and facilitation should be done on a site-by-site assessment, based on flow conditions, in order to decide on the optimal relaying density.…”
Section: Discussionmentioning
confidence: 82%
“…Liu, Weerman, Herman, Olff, & van de Koppel, 2012;Quan-Xing Liu et al, 2014;Snover & Commito, 1998; van de Koppel et al, 2008; de Koppel, Rietkerk, Dankers, & Herman, 2005). Natural mussel beds are also spatially structured with regards to sizes of individuals within, with the basal structure made by larger individuals with younger individuals being more motile (Wiegemann, 2005) and finding refuge within the matrix provided ( Commito et al, 2014;Bertolini, Montgomery, & O'Connor, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A clear example of spatially structured habitat, where habitat‐formers are cooperating to form self‐organised patterns according to different environments and neighbours size, is given by mussel beds (Commito et al, ; Commito, Gownaris, Haulsee, Coleman, & Beal, ; Liu, Weerman, Herman, Olff, & Koppel, ; Quan‐Xing Liu et al, ; Snover & Commito, ; van de Koppel, Rietkerk, Dankers, & Herman, ; van de Koppel et al, ). Natural mussel beds are also spatially structured with regard to sizes of individuals within, with the basal structure made by larger individuals with younger individuals being more motile (Wiegemann, ) and finding refuge within the matrix provided (Bertolini, Montgomery, & O’Connor, ; Commito et al, ).…”
Section: Introductionmentioning
confidence: 99%